Distribution of sagittal occlusal relationships in different stages of dentition - Emine KAYGISIZ; Lale TANER; Kahraman GUNGOR (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The aim of this study was to assess the distribution of sagittal occlusal relationships in different dentition periods in a Turkish sample group. In total, 1,110 patients (561 females, 549 males) aged 4.6-23 years were randomly chosen after intraoral clinical examination. The subjects were classified according to their sagittal occlusal relationships and four dentition stages -deciduous, early mixed, late mixed, and permanent dentition. The statistical significance of the occurrence of malocclusion types in dentition stages was evaluated by Chi-square and Fischer's exact tests. Class I malocclusion was observed at the highest rate in all dentition stages. Class III malocclusion was observed at the highest rate in the permanent dentition, whereas Class II malocclusion was observed at the highest rate in the late mixed dentition. The rates of Class I, II, and III malocclusions were similar in males and females. Our study reveals that the prevalence of malocclusion and need for orthodontic treatment has increased in the population towards the permanent dentition.